Inheritance Risk Management Towards the Sustainability of Global Family Businesses in Malaysia - Nehad Ibrahim Abd Alfatah Ineizeh; Murad Ali Al-Zaqeba; Ibrahim Fahad Sulaiman; Suhaib Al-Khazaleh; Ismail Yamin; Ohoud Khasawneh (Brighteredge Press Resources, 2026)
Non-Indexed Publication